2015
DOI: 10.2119/molmed.2015.00179
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Brain AMP-Activated Protein Kinase Attenuates Inflammation and Acute Lung Injury in Sepsis

Abstract: Sepsis and septic shock are enormous public health problems with astronomical financial repercussions on health systems worldwide. The central nervous system (CNS) is closely intertwined in the septic process but the underlying mechanism is still obscure. AMP-activated protein kinase (AMPK) is a ubiquitous energy sensor enzyme and plays a key role in regulation of energy homeostasis and cell survival. In this study, we hypothesized that activation of AMPK in the brain would attenuate inflammatory responses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
(54 reference statements)
2
9
0
Order By: Relevance
“…In addition, activation of AMPKα by IQC triggered apoptosis of bladder cancer cells . As an important regulator, AMPKα has been shown to have anti‐inflammatory actions . Our data confirmed that inhibiting the NF‐κB pathway by IQC depended on AMPKα.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, activation of AMPKα by IQC triggered apoptosis of bladder cancer cells . As an important regulator, AMPKα has been shown to have anti‐inflammatory actions . Our data confirmed that inhibiting the NF‐κB pathway by IQC depended on AMPKα.…”
Section: Discussionsupporting
confidence: 80%
“…Activation of AMPK has been shown to attenuate lung inflammation and the severity of lung injuries induced by LPS (50) and sepsis (51), as well as LPS-induced lung vascular endothelial permeability (52). AMPK is activated via phosphorylation of T172.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect of metformin in mice with lipopolysachharide (LPS)-induced septic shock and in ob/ob mice is mediated at least in part by AMPK activation [ 116 ]. In septic mice, AMPK activation by AICAR or metformin reduces the severity of sepsis-induced lung injury, enhances AMPK phosphorylation in the brain, and attenuates the inflammatory response [ 117 , 118 ].…”
Section: Roles Of Ampk In Innate and Adaptive Immune Responsesmentioning
confidence: 99%